The Palestinian-Arab minority in Israel, 1948-2000 : a political study - Ganim, Asʻad (State University of New York Press, 2001)
Relying on personal interviews and documentary evidence, Ghanem (political science, U. of Haifa; Peace Research Institute, Givat Haviva) examines the predicament of the Palestinian-Arab citizen in Israel who is doubly-marginalized: a minority in a Jewish state, and isolated from brethren living under the Palestinian Authority. The author shows that Israeli Arabs are hardly a monolithic group by profiling their divergent political and ideological streams in a historical context. An Israeli-Palestinian bi-national state is regarded as the solution to this situation as well as to the broader conflict. Tables summarize the Arab vote in local and Knesset elections. Annotation copyrighted by Book News Inc., Portland, OR.
Keywords: Palestinian Arabs -- Israel -- History.; Israel -- Ethnic relations.; HISTORY.; Ethnic relations; Palestinian Arabs; Israel; History